The merchant banking arena: with case-studies - Kellett, Richard (London ; Melbourne [etc.] ; New York : Macmillan ; St. Martin's P., 1967)
This book is an outline of how the London merchant banker have developed.
Includes bibliographical references "Notes" (p. [166]-170)
obn 23/01/2019
Loans
Keywords: Merchant banks